Assessing COVID-19 knowledge, attitudes, and practices among hospital employees: identifying sociodemographic determinants for improved public health strategies - Aljasim, Layla; Javed, Nargis Begum; Cordoba, Carlos; Alyaseen, Haider; Aljasim, Batool; Aljasim, Mariam; Cordoba, Magdalena; Bugis, Bussma A.; Al-Mohaithef, Mohammed (Frontiers in Public Health, 2024)
Background The working environment of healthcare institution during pandemic puts all hospital employees at high-risk of being exposed to contagious infections. An individual’s behavior and response are largely determined by their level of knowledge, attitudes and practices (KAP) toward a disease. Therefore, the present study aimed to evaluate and assess the KAP toward COVID-19 among hospital employees working in various positions and to identify the sociodemographic determinants associated with the level of KAP. Methods A cross-sectional survey was conducted from July 1 to July 15, 2020 in Almoosa Specialist Hospital, Alhasa, Eastern Province, Saudi Arabia in which 221 hospital employees with varied job titles participated. The data for demographics and history of COVID-19 exposure, KAP related to COVID-19 spread and prevention were collected online using a web-based platform (Survey Monkey). Student’s t-test/One-way ANOVA were used to compare total mean and standard deviation of KAP scores with demographic profiles and history of exposure. Results 89.1% employees knew that COVID-19 virus is mostly transmitted from human-to-human, and 76.0% employees acknowledged droplet transmission. 64.7% employees preferred to take a sick person with unconfirmed COVID-19 to a health facility. Physicians had higher knowledge scores for COVID-19 infection and non-medical employees had the lowest scores (7.47 ± 1.23 and 6.47 ± 1.44, respectively). Nurses had the highest practice scores and non-medical employees lowest practice score (6.16 ± 0.74 and 5.37 ± 1.14, respectively). Attitude scores were similar among all the employees. All employees reported an increase in hand-washing frequency and physical contact avoidance. Conclusion The study results revealed socio-demographic factors; level of education, nationality, and field of service are associated with COVID-19 KAP. The study highlights that there is a gap in the level of knowledge about COVID-19, especially among nonmedical employees. Targeted interventional programs need to be planned and implemented to improve COVID-19 awareness among non-medical employees.